UPAYA PREVENTIF TERHADAP TINDAKAN BULLYING DI SEKOLAH DASAR NEGERI 1 SUNGAI TIUNG BANJARBARU MENURUT PERSPEKTIF UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Khairunnisa Khairunnisa; Rahmi Hidayati; Rinto Widyanto; Sandi Rizky (LPPM Universitas Bina Bangsa, 2024)
Nowadays, we often hear about many legal incidents and even see them ourselves in society, one of which is the rise of bullying which is very rampant both among adults and children. Bullying will cause harm to the victim, whether physical or mental harm to a person, and often results in the loss of a person's life. In this case, it is hoped that many parties will be involved in preventing bullying, not only parents or those closest to them who will play a role in providing protection and prevention, but the government will also be involved in it. Regarding bullying actions that are often carried out in elementary schools involving children as victims or even as perpetrators, the government has created an Independent Curriculum, one of which includes the implementation of the Pancasila Student Profile Strengthening Project or known as P5. Activities are designed to strengthen efforts to achieve competence and character according to the Pancasila Student profile. It is hoped that the Independent Curriculum related to the implementation of the Pancasila Student Profile Strengthening Project can encourage and shape the character of young people so that they can carry out their role as good human beings.